2022
DOI: 10.3390/horticulturae8111081
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phytochemical and Nutrient Compounds from the Leaves and Seeds of Moringa oleifera and Moringa peregrina

Abstract: Moringa oleifera and M. peregrina are robust and fast-growing trees. These trees are considered some of the most highly valued trees worldwide because of their properties and uses. This study aimed to investigate and determine the content of phytochemical and nutrient compounds in the fresh leaves and the mature seeds of both M. oleifera and M. peregrina. The experimental data analysis showed that all four extracts were rich in proximate minerals, fatty acids (FA), and un-saponified and polyphenolic components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
0
1
0
1
Order By: Relevance
“…Another study reported the ethanolic extract of M. oleifera contained p-Coumaric acid and quercetin [ 52 ]. Chlorogenic acid, catechin, caffeic acid, rutin, quercetin, and kaempferol were identified in the leaves of M. oleifera using HPLC analysis [ 53 ]. M. oleifera leaves dried at four different temperatures were analyzed using high-performance liquid chromatography in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported the ethanolic extract of M. oleifera contained p-Coumaric acid and quercetin [ 52 ]. Chlorogenic acid, catechin, caffeic acid, rutin, quercetin, and kaempferol were identified in the leaves of M. oleifera using HPLC analysis [ 53 ]. M. oleifera leaves dried at four different temperatures were analyzed using high-performance liquid chromatography in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaman kelor diakui sebagai sumber fitokimia dan nutrisi yang penting, sehingga dapat digunakan sebagai bahan tambahan dalam industri makanan dan farmasi (31). Penelitian lain menjelaskan dalam daun kelor terdapat senyawa beta sitosterol yang mampu meningkatkan fungsi usus dalam menyerap lemak atau kolesterol sehingga kadar kolesterol yang beredar dalam darah dapat diturunkan (32).…”
Section: Bahasanunclassified